Activity Based Management Change Order Model-Based Economic Value Added Through The Effectiveness And Efficiency To Improve The Financial Performance Of Building Construction Projects In Surabaya City - Witjaksana, Budi (Archives of Business Research, 2019)
The purpose of this study to determine the effect of Activity-Based Management Change Order (ABMCO) and Economic Value Added (EVA), to the effectiveness and efficiency of building construction projects. To know the impact of efficacy and to the performance of doing construction project; to see the impact of EVA on the performance of doing construction project; as well as to determine the influence of ABMCO affect the EVA building construction project. This research approach uses quantitative and qualitative approaches commonly called Mixed Methode. The population in this study is the Contractor registered in the Construction Services Development Board of Indonesia (LPJK) of Surabaya as much as 121 contractors. The method of sample selection in this study using a non-probability sampling method with a purposive sampling technique. The criteria used in this study are (1) Have K1-K3 Classification; (2) The maximum number of project work during 2016 is 2.5 Billion; and (3) Minimum 1 (one) time to work on the project in 2016. The sample used in this research is 93 (ninety-three) contractors. The analysis technique chosen to analyze the data and test the hypothesis in this research is The Structural Equation Model (SEM) with a Partial Least Square (PLS) software. The result of this research can conclude that the Activity Based Management Change Order variable (ABMCO) and Economic Value Added (EVA) have a significant effect on the effectiveness and efficiency of building construction project while the Activity-Based Management Change Order (ABMCO) variable has no significant impact on construction project performance. Effectiveness significantly influence the performance of building construction projects; Efficiency has no significant effect on the performance of building construction projects, and Economic Value Added (EVA) variables significantly influence the performance of doing construction projects and Activity-Based Management Change Order (ABMCO) variables significantly affect Economic Value Added (EVA).